The Combination Effect of Chemotherapy Drug with Febuxostat and Curcumin on Colon Cancer Cell line (LS174T) - Ali M. Jaafar Abdulsahib; Rana Ayad Ghaleb; Nisreen Jalal Mohammed (Medical Journal of Babylon, 2025)
Background: Colorectal cancers are the 3rd highest commonly discovered form of cancer worldwide. The outcomes of various studies have revealed that cancer cells growth has been affected in response to treatment. In this study, the in vitro cytotoxic effects of different drug combinations [5-fluorouracil (5-FU), curcumin, and febuxostat] were measured by crystal violet method. The results showed significant anticancer activity on LS174T colorectal cancer cell line at different combinations. Objective: This study aimed to assess the cytotoxic effect of different combinations of 5-FU, curcumin, and febuxostat on colorectal cancer LS174 cell line. Materials and Methods: For 24 h, the human colon cancer cell line LS174T was given a variety of doses of combinations of 5-FU, febuxostat, and curcumin. Crystal violet assay was used to assess the cytotoxicity of the combined agents extract against colon cancer cells. Results: 5-FU, curcumin, and febuxostat when used in different combinations concentrations, showed respectable anticancer effect on colorectal cancer LS174T cell line. Conclusion: The current study indicated that the good anticancer effects of combined agents when used to treat colorectal cancer.